2011
DOI: 10.1186/1742-2094-8-185
|View full text |Cite
|
Sign up to set email alerts
|

Low ficolin-3 levels in early follow-up serum samples are associated with the severity and unfavorable outcome of acute ischemic stroke

Abstract: BackgroundA number of data indicate that the lectin pathway of complement activation contributes to the pathophysiology of ischemic stroke. The lectin pathway may be triggered by the binding of mannose-binding lectin (MBL), ficolin-2 or ficolin-3 to different ligands. Although several papers demonstrated the significance of MBL in ischemic stroke, the role of ficolins has not been examined.MethodsSera were obtained within 12 hours after the onset of ischemic stroke (admission samples) and 3-4 days later (follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 51 publications
7
48
0
Order By: Relevance
“…Moreover, ficolin-3 has been shown to be decreased in patients with diabetic nephropathy [31], and that it varied significantly between type 2 diabetes patients and controls [32]. Recently, our group reported that concentrations of ficolin-3 were significantly decreased in both the admission and in the follow-up samples of patients with definite ischemic stroke as compared to healthy subjects [33]. An inverse correlation was observed between low ficolin-3 levels and high concentration of S100beta, an indicator of the size of cerebral infarct suggesting that ficolin-3 contributes to the pathogenesis of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ficolin-3 has been shown to be decreased in patients with diabetic nephropathy [31], and that it varied significantly between type 2 diabetes patients and controls [32]. Recently, our group reported that concentrations of ficolin-3 were significantly decreased in both the admission and in the follow-up samples of patients with definite ischemic stroke as compared to healthy subjects [33]. An inverse correlation was observed between low ficolin-3 levels and high concentration of S100beta, an indicator of the size of cerebral infarct suggesting that ficolin-3 contributes to the pathogenesis of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data are strongly suggesting an important role for MBL and/or the lectin pathway in the pathogenesis of brain injury 12,27,43,45 . Our data provide strong support to the concept that MBL inhibition may be a relevant therapeutic target in humans, one with a wide therapeutic window of application.…”
Section: Discussionmentioning
confidence: 99%
“…

Objectives: To assess the involvement of ficolin-3, the main initiator of the lectin complement pathway (LCP), in subarachnoid hemorrhage (SAH) pathology and outcome.

Methods: In this preliminary exploratory study, plasma concentration of ficolin-3 and of ficolin-3-mediated functional LCP activity was measured, along with that of other LCP initiators (mannose-binding lectin, ficolin-2, and ficolin-1), C3 activation products, and soluble C5b-9 terminal complex, in a prospective cohort of 39 patients with SAH and 20 healthy controls. [6][7][8][9][10] In blood, LCP initiators form complexes with associated serine proteases (MASPs) and with nonenzymatic proteins named sMAP and MAP-1. Notably, however, ficolin-3-mediated functional LCP activity was reduced.

…”
mentioning
confidence: 99%